Evaluasi Kapasitas Jaringan Irigasi Lanrae Pada Kebutuhan Air Sawah di Kabupaten Barru - Muhlis; Rahmawati; Andi Bustan Didi (Jurnal Karajata Engineering, 2024)
Irrigation is an infrastructure to increase land productivity and increase the intensity of annual harvests, the availability of adequately controlled irrigation water is an input to increase crop production. The Lanrae irrigation area which has 1400 Ha of agricultural rice fields that need water, Lanrae is one of the areas located in Nepo Village, Mallusetasi District, Barru Regency. This research aims to meet the needs of irrigation water for farmers who usually experience crop failure due to lack of irrigation water and to increase the potential of existing agricultural products in the Lanrae area in particular and in Barru Regency in general as well as to overcome complaints from farmer groups who experience a lack of water to increase yields. harvest. This research was conducted in the Lanrae Area, Mallusetasi District, Barru Regency, which was carried out from January to March 2017 using quantitative methods. The results of the research on weirs and irrigation in the Lanrae area of Barru Regency showed that the availability of water in the Lanrae river is currently still sufficient to meet the needs for irrigation water in the Lanrae irrigation area and the utilization of irrigation networks for irrigation water services is not optimal and the efficiency of irrigation water use is very low. As well as the use of irrigation water in the upstream areas tends to be excessive and the use of irrigation water in the middle and even downstream areas is very short of water.